Nanny [videorecording (DVD)] - Jusu, Nikyatu; Diop, Anna, 1988-; Monaghan, Michelle; Walls, Sinqua; Spector, Morgan, 1980-; Decker, Rose; Uggams, Leslie (Criterion collection, 2023)
Aisha, a Senegalese immigrant, takes a job as a nanny for a wealthy white family in New York City. Separated from her son and casually exploited by her employers, Aisha finds herself consumed by unsettling visions and a growing rage, one that could either destroy or empower her.